Ocular and adnexal anomalies in craniofacial microsomia: Type and prevalence in a multicentre cohort study. Issue 10 (October 2021) - Rooijers, W.; Renkema, R.W.; Loudon, S.E.; Khoshnaw, T.; Padwa, B.L.; Dunaway, D.J.; Koudstaal, M.J.; Forrest, C.R.; Caron, C.J.J.M.
Abstract: The aim of this multicentre retrospective cohort study was to describe and categorize the types of ocular and adnexal anomalies seen in patients with craniofacial microsomia (CFM) and to determine their prevalence. In addition, the relationship between the OMENS-Plus and Pruzansky–Kaban classification for each patient and the presence of ocular anomalies was investigated. A total of 881 patients with CFM from four different craniofacial centres were included. Data on ocular anomalies were gathered from the patient charts. Ocular anomalies were present in 33.9% of patients. Four subgroups of ocular and adnexal anomalies were identified. Type I ocular anomalies were present in 22.2%, type II in 19.0%, type III in 18.4%, and type IV in 14.5%. Several potentially preventable and treatable ocular anomalies were identified. Higher OMENS-Plus classification orbit and soft tissue scores and Pruzansky–Kaban classification mandible scores were associated with an increased risk of ocular anomalies. Based on these results and the clinical implications ocular anomalies may have, we underline the importance of targeted ophthalmological screening in CFM. Healthcare professionals should be aware of the possibility of ocular anomalies in these patients, especially during the critical period for visual development.